Combined bottom‐up and top‐down pressures drive catastrophic population declines of Arctic skuas in Scotland. (28th August 2018) - Perkins, Allan; Ratcliffe, Norman; Suddaby, Dave; Ribbands, Brian; Smith, Claire; Ellis, Pete; Meek, Eric; Bolton, Mark
Abstract: Understanding drivers of population change is critical for effective species conservation. In the northeast Atlantic Ocean, recent changes amongst seabird communities are linked to human and climate change impacts on food webs. Many species have declined severely, with food shortages, and increased predation reducing productivity. Arctic skua Stercorarius parasiticus, a kleptoparasite of other seabirds, is one such species. The aim of the study was to determine relative effects of bottom‐up and top‐down pressures on Arctic skuas across multiple colonies in a rapidly declining national population. Long‐term monitoring data were used to quantify changes in population size and productivity of Arctic skuas, their hosts (black‐legged kittiwake Rissa tridactyla, common guillemot Uria aalge, Atlantic puffin Fratercula arctica, Arctic tern Sterna paradisaea ) and an apex predator (great skua Stercorarius skua ) over 24 years (1992–2015) in Scotland. We used digital mapping and statistical models to determine relative effects of bottom‐up (host productivity) and top‐down (great skua density) pressures on Arctic skuas across 33 colonies, and assess variation between three colony types classified by host abundance. Arctic skuas declined by 81% and their hosts by 42%–92%, whereas at most colonies great skuas increased. Annual productivity declined in Arctic skuas and their hosts, and reduced Arctic skua breeding success was a driver of the species' population decline. Arctic skua productivity was positively associated with annual breeding success of hosts and negatively with great skua density. Intercolony variation suggested Arctic skua trends and productivity were most sensitive to top‐down pressures at smaller colonies of host species where great skuas had increased most, whereas bottom‐up pressures dominated at large colonies of host species. Scotland's Arctic skua population is declining rapidly, with bottom‐up and top‐down pressures simultaneously reducing breeding success to unsustainably low levels. Marine food web alterations, strongly influenced by fisheries management and climate change, are driving the decline, and this study demonstrates severe vulnerability of seabirds to rapid change in human‐modified ecosystems. Potential but untested conservation solutions for Arctic skuas include marine protected areas, supplementary feeding within colonies and management of great skuas. Abstract : This article demonstrates bottom‐up and top‐down pressures simultaneously reducing Arctic skua breeding success to unsustainably low levels, pushing the species towards local extinction. The authors' novel use of long‐term seabird monitoring datasets across multiple colonies revealed differences in relative strength of these pressures between colony types, helping to inform conservation policy.